Violence at School and Bullying in School Environments in Peru: Analysis of a Virtual Platform - Arhuis-Inca, Wendy; Ipanaqué-Zapata, Miguel; Bazalar-Palacios, Janina; Quevedo-Calderón, Nancy; Gaete, Jorge (Frontiers in Psychology, 2021)
Background: School violence and bullying are prevalent problems that affect health in general, especially through the development of emotional and behavioural problems, and can result in the deterioration of the academic performance of the student victim. The objective of this study was to determine the prevalence rates of aggressive behaviours according to types of school violence and bullying, sociodemographic characteristics and variation by department, region and time in the period between 2014 and 2018 in Peru. Method: The design was observational and cross-sectional based on data from the Specialized System for Reporting Cases of School Violence (Sistema Especializado en Reporte de Casos sobre Violencia Escolar - SíseVe) in Peru, which covers a population of 23,641 students at the initial, primary and secondary levels of Basic Regular Education (Educación Básica Regular - EBR), for the 2014-2018 period. The prevalence rates of the different types of school violence and bullying, the sociodemographic characteristics, and the variation by department, region, and time in the period between 2014 and 2018 were estimated. Results: Psychological violence/bullying occurred at higher prevalence rates (185.8 and 62.6 per 100,000 residents). Women from public institutions reported greater sexual violence, mostly by teachers (67.8%) than by other students (32.2%). The Selva region had the highest prevalence rate of sexual violence (10.1 per 100,000 residents). The departments of Tacna and Piura had the highest and lowest rates of psychological/verbal violence and bullying in 2018 (95.79 and 25.31 per 100,000 residents). Conclusions: Psychological/verbal violence and bullying is highly prevalent among students; women report being victims of sexual violence by administrative personnel of public institutions. The Selva region had the highest rate of sexual violence, and Piura and Tacna had the highest and lowest rates of violence and psychological/verbal bullying. Based on these results, it is suggested to conduct evidence-based prevention programmes in Peruvian schools to reduce these social problems.